Implementation of RSA Algorithm For Securing Patient Data using QR Code Technology - Cobantoro, Adi Fajaryanto; Wicahyono, Fadhlullah Yoga; Zulkarnain, Ismail Abdurrozzaq (Jurusan Teknik Informatika Fakultas Teknik Universitas Trunojoyo Madura, 2025)
The advancement of digital technology demands improved security systems, especially in protecting users’ personal data. One sector that heavily relies on data confidentiality is the healthcare sector, where patient information must be safeguarded from potential leaks and misuse. This study aims to implement the RSA (Rivest-Shamir-Adleman) cryptographic algorithm in the patient registration system at the dental clinic of Regunawati Cahyaningsih. RSA was chosen for its asymmetric nature and its ability to ensure data security through the use of public and private key pairs. Additionally, this study integrates QR Code technology as a medium for accessing encrypted data, streamlining and accelerating the data authorization process. The encryption process is applied to important information such as NIK, name, address, phone number, and medical records before being stored in the database. Based on the testing results, the system demonstrated excellent performance in terms of functionality, algorithm accuracy, and display speed. Whitebox testing confirmed the accuracy of the RSA algorithm implementation with 100% accuracy. Performance testing using the Largest Contentful Paint (LCP) metric showed very fast load times, ranging from 0.5 to 2.3 milliseconds, with a performance score of 100, making the system highly responsive and optimal in terms of user experience. Therefore, RSA is proven to be effective in enhancing patient data security and maintaining confidentiality within a web-based clinical information system.Keywords: Rivest-Shamir-Adleman Algorithm, Patient Data Security, Whitebox Testing, QR Code